The risk of micro and macrovascular disease in Egyptian patients with diabetes and peripheral arterial disease. Issue 2 (4th March 2021) - Assem, Maha; Mousa, Shrook; Abdelhamid, Alaa; Amin, Samar; Elsamadony, Ayman; El-Sebaee, Eman; Saif, Aasem; Elsawy, Shereen
ABSTRACT: Aim : The aim of this study was to assess the prevalence of micro- and macrovascular disease in Egyptian patients with diabetes mellitus (DM) and peripheral arterial disease (PAD). Methods : The study included 161 Egyptian patients with DM and PAD (91.3% had type 2 DM and 67.1% were females). Mean diabetes duration was 14.2 ± 5.2 years. Full history, clinical and fundus examination as well as laboratory investigations were done. PAD was diagnosed through assessment of ankle/brachial index (ABI) by Doppler ultrasonography. Results : ABI was <0.9 in 33.5% and >1.3 in 66.5% of patients. A significant positive correlation was found between abnormal ABI and diabetes duration, ischemic heart disease (IHD), diabetic retinopathy and neuropathy, foot ulcers, elevated blood pressure (BP), creatinine, urine albumin/creatinine ratio (ACR) and triglycerides and a significant negative correlation with HDL. Multivariate regression analysis revealed that the independent predictors for PAD in patients with ABI< 0.9 were neuropathy, creatinine, triglyceride, LDL, urine ACR and low HDL, and in patients with ABI >1.3 were IHD, neuropathy, elevated diastolic BP and triglyceride. Conclusion : The risk of micro- and macrovascular disease is high in Egyptian patients with diabetes and PAD. Early diagnosis and good control of risk factors could reduce PAD progression.